Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Kemampuan Komunikasi Matematis Siswa Kelas XI IPA MAN Kota Padang - Irwan, Irwan (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research was aimed at finding out (1) mathematical communication skills, and (2) mathematical communication skills of students based on high, medium, and low knowledge. This research is a quasiexperimental research. Sample of this research is students at XI IPA1 and XI IPA2 MAN Padang. The accumulation of data using test and the analysis of data by statistical. The results showed that (1) mathematical communication skills of students who are taught by TTW better than conventional learning, (2) mathematical communication skills of students initial knowledge high, medium, and low are better taught by TTW than conventional learning